Predição da geração entrópica e avaliação do impacto do estilo de vida e das condições ambientais na longevidade humana - Inara Magno Nogueira (2021)
The laws of thermodynamics can be applied to the analysis of biological systems. Studies in the literature apply the properties of thermodynamics to describe the life expectancy of the human body as a function of the level of physical activity and habits of each individual, especially considering the second law of thermodynamics. The analysis of these studies shows that there may be a theoretical contradiction created between entropy generation and lifespan in the human body. According to the literature, physical activity decreases longevity, since it elevates cumulative entropy generation, that is, it incites disorder in the system, bringing about early failure. This opposes medical recommendations of maintaining the good habit of exercising, seeking quality of life and increase in lifespan. The main objective of this paper is to propose a simplified mathematical model between longevity and entropy generation in the human body, when exposed to physical activity, different food habits and variable environmental conditions. After a search for models presented in the literature, a verification and comparison of the results previously published was done, as was a survey of the main variables used. Thereby, a new model as comprehensive as possible was constructed. This new model was validated comparing different conditions and individuals. A life expectancy of 70.21 years for a sedentary male has been considered, resulting in an accumulative entropy generation of 11,327 kJ/kg.K. Thus, considering a fixed limit of entropy generation, as suggested by previous authors, life expectancies of 56.29 years for an active person and 47.04 years for an athlete were found. Furthermore, it was found that cold places and a greater ingestion of fat would positively affect life expectancy. These obtained results show a need for additional assessments and considerations to make the modeling more accurate. Based on data relating the variation in expectations generated with the practice of physical activity, it is possible to see that there should actually be an increase in the limit of entropy generation for those who exercise regularly. Evaluations have shown that there may actually be an increase of up to approximately 40% in accumulated entropy generation for the relationship between this practice and longevity. After all the analyses and in order to maintain the likelihood of the model, it is suggested that the principle of cumulative limit of entropy generation should be relaxed in function of lifestyle and type of exercise performed during life, differently from what is argued in the literature. In this way, each individual would have his or her entropic limit defined by characteristics and habits taken throughout life.